2020
DOI: 10.3389/fendo.2020.571037
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Poor Outcomes of Diabetes Patients With COVID-19: A Single-Center, Retrospective Study in Early Outbreak in China

Abstract: Background: Diabetes has been found to increase severity and mortality under the current pandemic of coronavirus disease of 2019 (COVID-19). Up to date, the clinical characteristics of diabetes patients with COVID-19 and the risk factors for poor clinical outcomes are not clearly understood. Methods: The study was retrospectively carried out on enrolled diabetes patients with laboratory confirmed COVID-19 infection from a designated medical center for COVID-19 from January 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 19 publications
3
31
0
4
Order By: Relevance
“…Nevertheless, for diabetes, there is a slightly higher association in the Centre, South, and Yucatan peninsula. The associations have also been reported in other studies in other geographical regions [31][32][33], and although it is still under study, they may be associated with inflammatory stages [34]. Finally, the proportion of individuals between 10 and 39 years old has a relatively similar effect throughout Mexico.…”
Section: Discussionsupporting
confidence: 78%
“…Nevertheless, for diabetes, there is a slightly higher association in the Centre, South, and Yucatan peninsula. The associations have also been reported in other studies in other geographical regions [31][32][33], and although it is still under study, they may be associated with inflammatory stages [34]. Finally, the proportion of individuals between 10 and 39 years old has a relatively similar effect throughout Mexico.…”
Section: Discussionsupporting
confidence: 78%
“…Our findings correlate with previous evidence that found an association of DM with a higher risk of severe pneumonia in 16-40%. 26,28 They were also found in the literature to have a greater occurrence of ARDS, acute heart injury, acute kidney injury, septic shock, and disseminated intravascular coagulation. 11 McGurnagha et al reported that DM was associated with an OR of 1.395 for fatal or critical care unit treated COVID-19.…”
Section: Effect Of Possible Risk Factors On the Severity And Outcome In Diabetic Groupmentioning
confidence: 93%
“…To examine the association between metformin use and other outcomes, we conducted a further meta-analyses of two (33,52), five (35,38,39,41,48,49), and four (29)(30)(31)47) studies estimating the association between metformin use and risk of intubation, deterioration, and hospitalization. The pooled ORs of metformin use with intubation, deterioration, and hospitalization were 0.94 (95% CI, 0.77-1.16; I 2 = 0.0%), 2.04 (95% CI, 0.65-6.34; I 2 = 79.4%), and 0.73 (95% CI, 0.53-1.00; I 2 = 16.8%), respectively (Supplementary Figures 2-4).…”
Section: Metformin Use and Other Covid-19 Outcomesmentioning
confidence: 99%